LITERATURE REVIEW PENILAIAN FAKTOR YANG MENENTUKAN DALAM BUDAYA KESELAMATAN PASIEN DI FASILITAS PELAYANAN KESEHATAN - Agung Purnomo; Yuly Peristiowati; Heri Suroso (Journal of Nursing Care and Biomolecular, 2022)
Introduction: Safety has become a global issue including in hospitals. There are five important aspects related to safety at home, namely safetthey, safety of workers or health workers, the safety of buildings and hospital equipment that have an impact on patient and staff safety, environmental safety which has an impact on the environment and home business safety related to hospital life. The purpose of this study is to identify and analyze the research instruments used and to find out what dimensions affect the importance of safety in service facilities. Methods: The preparation of the literature review went through several stages: making several methods with PICOS, and conducting a literature review using a prism, such as searching, selecting, selecting, and determining articles according to the inclusion criteria. Results: Search articles using Google Scholar, Proquest, Wiley, Springer, and Oxford Academic databases. Results: 5 Google Scholar articles, 5 Proquest articles, 5 Wiley articles, 3 Oxford articles and 2 Spinger articles. The results of a review of 20 journals on the determining factors in patient safety culture in health care facilities. Discussion: several factors that determine the safety of health service safety in facilities, namely Team work, Work environment, management support, Staffing, Expectations and actions of supervisors, Feedback and communication,. Team work within units, Frequency of reported occurrences, and Non-punitive response to errors.   Keywords: Assessment, Culture, Health facilities, Safety.